Amphiphilic polymer as well as preparation method and application thereof

By designing amphiphilic polymers and introducing them into the hydrogel system, forming a folded chain structure, the problem of insufficient mechanical strength and toughness of the hydrogel is solved, and the improvement of strength, stiffness and toughness is achieved, and its application scope is broadened.

CN119823383AActive Publication Date: 2025-04-15ANHUI UNIV

Patent Information

Application Number
CN202510036841.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing hydrogels have low mechanical strength and toughness, which limits their applications in flexible electronic devices, software robots, and tissue engineering.

Method used

By designing an amphiphilic polymer whose structure contains hydrophilic and hydrophobic groups, a folded chain structure is formed through Michael addition reaction, and introduced into the hydrogel system to enhance its mechanical properties.

Benefits of technology

Multiple improvements in strength, stiffness and toughness of the hydrogel are achieved, significantly improving its mechanical properties, making it more suitable for use in high-demand application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823383A_ABST
    Figure CN119823383A_ABST
Patent Text Reader

Abstract

The invention discloses an amphiphilic polymer as well as a preparation method and application thereof, the structural formula of the polymer is # imgabs0 #, n is 70-636, R is saturated fat alkyl, and the polymer is of a folded chain structure and is obtained by carrying out Michael addition reaction on double bonds, thioether and amino. The invention further discloses application of the amphiphilic polymer to improvement of the mechanical property of hydrogel, and the polymer has hydrophilic groups and hydrophobic groups at the same time and can be self-assembled into a regular and ordered folded chain structure. After the polymer is introduced into a hydrogel system, the strength, rigidity and toughness of the hydrogel are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to an amphiphilic polymer and a preparation method and application thereof. Background Art

[0002] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel. Due to the presence of a cross-linked network, hydrogels can swell rapidly and retain a large amount of water without dissolving. The amount of water absorbed is closely related to the degree of cross-linking of the hydrogel. Generally speaking, the higher the degree of cross-linking of the hydrogel, the lower the water absorption. Therefore, the degree of cross-linking can be adjusted to obtain hydrogels with a water content ranging from a few percent to as high as ninety-nine percent. Because of this characteristic, the aggregation state of the hydrogel is neither completely solid nor completely liquid, that is, the hydrogel has both the behavior of a solid that can maintain its shape and volume under certain conditions, and the behavior of a liquid that allows solutes to diffuse or penetrate through the hydrogel.

[0003] In the hydrogel network, water molecules are tightly bound to the hydrophilic groups of the polymer chains. Therefore, the hydrogel material has strong plasticity, good fluid thermodynamic properties and biocompatibility, and has great application prospects in the fields of flexible electronic devices, soft robots, tissue engineering, etc. However, due to the uneven network and the large amount of water contained, the strength and toughness of the hydrogel are generally not ideal, which limits its application. For example, many biological hydrogels in animals, such as muscles, heart valves, cartilage and tendons, are required to have extremely high mechanical properties, including extremely tough, strong, elastic, adhesive and fatigue-resistant properties. These mechanical properties are also crucial for the various applications of hydrogels.

[0004] The poor mechanical properties of conventional hydrogels are due to several inherent characteristics. One is the heterogeneity of polymer density distribution and chain length in the polymer network between crosslinking points. Therefore, hydrogels are susceptible to stress concentration when loaded, which can induce cracks. Another is the poor toughness of rubber due to the lack of energy dissipation mechanism, resulting in low resistance to crack propagation. In addition, conventional hydrogels are usually rich in water, and the low solid loading capacity further leads to weak mechanical properties.

[0005] The important mechanical properties of hydrogels are toughness - the ability to resist defect expansion, characterized by fracture energy Γ, stiffness - elastic modulus E, and strength - fracture strain ε. For a simple polymer network material, these mechanical properties are interrelated and conflicting. The increase in elastic modulus and strength leads to a decrease in deformation capacity and toughness. However, the means of strengthening or toughening hydrogels often reduce the stretchability of hydrogels, further limiting their scope of use.

[0006] One of the main obstacles to the practical application of hydrogels is their low mechanical strength and toughness. Since 2000, many breakthroughs have been made in the development of improving the mechanical strength and toughness of hydrogels, great progress has been made in the research of soft materials, and our understanding of their failure mechanisms has become deeper. Currently, the commonly used strategies for strengthening and toughening hydrogels are: fiber / fabric reinforcement, design of double network reinforcement, introduction of supramolecular interactions, solvent replacement reinforcement, and design of well-arranged microscopic hydrogels. Although the use of these methods makes it possible to improve the strength and toughness of hydrogels at the same time, the above strategies often have one or more limitations, such as complex synthesis process, limited reinforcement, lack of versatility, etc., and the preparation of hydrogels with both strength and toughness is still a huge challenge.

[0007] Therefore, developing a universal strategy for preparing hydrogels with both strength and toughness is of great practical value. Summary of the invention

[0008] The technical problem to be solved by the present invention is how to simultaneously improve the strength and toughness of the hydrogel.

[0009] The present invention solves the above technical problems through the following technical means:

[0010] An amphiphilic polymer having a structural formula of one of the following:

[0011]

[0012] Wherein, n is 70-636, and R is a saturated fatty alkyl group.

[0013] Preferably, n=70-266.

[0014] Preferably, the weight average molecular weight Mw of the amphiphilic polymer is 30,000-270,000; R in the structural formula is -(CH2) 10 -or -(CH2)6-.

[0015] Preferably, the amphiphilic polymer is an amphiphilic diene monomer With alkyl monomers containing disulfide groups Or alkyl monomer containing di-secondary amine groups Obtained by Michael addition reaction, R is a saturated fatty alkyl group.

[0016] The present invention also provides a method for preparing the amphiphilic polymer, comprising: The amphiphilic polymer is obtained by a Michael addition reaction with an alkyl monomer containing a disulfide group or an alkyl monomer containing a di-secondary amine group; wherein the structural formula of the alkyl monomer containing a disulfide group is The structural formula of the alkyl monomer containing di-secondary amine groups is R is a saturated fatty alkyl group.

[0017] The method has the advantages of simple preparation method and mild reaction conditions.

[0018] Preferably, the molar ratio of the amphiphilic diene monomer, the disulfide group-containing alkyl monomer or the di-secondary amine group-containing alkyl monomer is 1 to 1.2: 1. The molecular weight of the amphiphilic polymer can be regulated by the feed ratio.

[0019] Preferably, the temperature for the reaction of the amphiphilic diene monomer with the alkyl monomer containing a disulfide group is room temperature, and the time is 24 hours; the temperature for the reaction of the amphiphilic diene monomer with the alkyl monomer containing a di-secondary amine group is 70-80° C., and the time is 24 hours; the alkyl monomer containing a disulfide group is 1,10-decanedithiol; the alkyl monomer containing a di-secondary amine group is N,N'-dimethyl-1,6-hexanediamine; the initial concentration of the amphiphilic diene monomer in the system is between 20 mg / mL and 100 mg / mL.

[0020] If the monomer concentration is too high, after the intense Michael addition reaction, the molecular weight of the amphiphilic polymer obtained is too large, and the system viscosity is also too large. If the monomer concentration is too low, it is difficult for the chain free radicals to capture the monomers during the chain growth stage, resulting in a small molecular weight of the amphiphilic polymer and a wide molecular weight distribution. Therefore, the concentration of the amphiphilic diene monomer should be controlled in a suitable range to obtain an amphiphilic polymer with a moderate molecular weight and molecular weight distribution.

[0021] Preferably, the ratio of the amount of the amphiphilic diene monomer to the solvent used in the reaction is 3 g:40 mL.

[0022] Preferably, the solvent used in the reaction is DMF.

[0023] In the technical scheme of the present invention, an amphiphilic diene monomer and a long alkyl chain monomer containing a thioether or an amino group are dissolved in DMF, and a polymer having both a hydrophilic group and a hydrophobic group and a folded chain tendency is obtained due to the Michael addition reaction between the two double bonds of the amphiphilic diene monomer provided by the present invention and the thioether or the amino group.

[0024] Preferably, the catalyst used in the Michael addition reaction is a mixture of one or more of the organic bases tetramethylguanidine, triethylamine, and 1,8-diazabicycloundec-7-ene, and the molar ratio of the amphiphilic diene monomer to the organic base is 1:0.2.

[0025] The invention also provides an application of the amphiphilic polymer in preparing a hydrogel.

[0026] Preferably, the hydrogel is a polyacrylamide hydrogel.

[0027] The present invention also provides a high-strength and high-toughness hydrogel, which is prepared by using raw materials including the amphiphilic polymer and hydrogel monomers.

[0028] Since the amphiphilic polymer has double bonds at both ends, it can be introduced into the hydrogel system by a simple polymerization reaction. And based on the tendency of forming folded chains given by the amphiphilic polymer in the molecular structure design stage, it forms a regular and orderly folded structure under static conditions, and the presence of physical crosslinking points improves the strength of the hydrogel. When subjected to external forces, the regular phase structure formed by the folded chain absorbs huge energy to achieve the unfolding deformation and stretching of its own folded chain structure, greatly increasing the chain length between the crosslinking points. At the same time, due to the strong interaction between the structural units--the existence of hydrogen bonds and Π-Π stacking interactions, the folded chain is used as an effective energy dissipation site. Therefore, the introduction of amphiphilic polymers can achieve multiple improvements in hydrogel strength, stiffness and toughness.

[0029] The present invention also provides a method for preparing the high-strength and high-toughness hydrogel, comprising using the amphiphilic polymer and the hydrogel monomer as raw materials to perform a photo-initiated polymerization reaction to obtain the high-strength and high-toughness hydrogel.

[0030] The amphiphilic polymer has double bonds at both ends, and after being uniformly mixed with the hydrogel monomer and the photoinitiator at the molecular level, a hydrogel based on the amphiphilic polymer is obtained by photoinitiated polymerization. The strength and toughness of the hydrogel obtained by uniformly mixing the amphiphilic polymer prepared by the present invention with the hydrogel monomer and undergoing photoinitiated polymerization are greatly improved.

[0031] By designing and synthesizing a class of amphiphilic polymers at the molecular level and introducing them into the hydrogel system, the mechanical properties of the hydrogel can be improved. In addition, the strengthening and toughening effect of the amphiphilic polymer can also be regulated by controlling the structure and molecular weight of the polymer.

[0032] Preferably, the molar ratio of the amphiphilic polymer to the hydrogel monomer is 1:2000-20000; the molar ratio of the photoinitiator to the hydrogel monomer is 7:10000; and the hydrogel monomer is acrylamide.

[0033] Preferably, the molar ratio of the amphiphilic polymer to the hydrogel monomer is (0.005% to 0.05%):1; if the molar ratio of the added amphiphilic polymer is too high, the polymer is difficult to disperse, and the constructed hydrogel has obvious unevenness. If the molar ratio of the added amphiphilic polymer is too low, the hydrogel may not have obvious strengthening and toughening effects.

[0034] Preferably, during the reaction, the solid content of the mixed reaction liquid formed by the amphiphilic polymer and the hydrogel monomer is 408 mg / mL to 568.9 mg / mL.

[0035] Preferably, the conditions for the photo-initiated polymerization reaction are: the temperature is room temperature and the time is 20 minutes.

[0036] Preferably, the method for preparing the high-strength and high-toughness hydrogel comprises the following steps:

[0037] (1) Dissolution of the amphiphilic polymer: Using DMF or water as solvent, weigh the amphiphilic polymer and add it to the solvent, and heat and stir at 60-70°C for 3 h;

[0038] (2) According to the molar ratio of the amphiphilic polymer to the hydrogel monomer AM of 0.005% to 0.05%:1, the amphiphilic polymer solution is mixed with the hydrogel monomer AM, a photoinitiator is added, and an excitation light source of 395 nm is used for irradiation for 20 minutes to obtain the high-strength and high-toughness hydrogel.

[0039] Preferably, the method for preparing the amphiphilic diene monomer comprises the following steps: Acryloyl chloride A nucleophilic substitution reaction occurs to obtain;

[0040] Preferably, the molar ratio of 3,5-diaminobenzoic acid to acryloyl chloride is 1:2-2.2; by controlling the molar amount of acryloyl chloride to be twice or more than twice of 3,5-diaminobenzoic acid, two hydrogen atoms on two primary amines can be replaced to obtain an amphiphilic diene monomer.

[0041] Preferably, the conditions of the nucleophilic substitution reaction are: temperature of 0 to 5° C. and time of 2 to 4 h.

[0042] The amphiphilic diene monomer can be obtained only through a nucleophilic substitution reaction, and has the advantages of a short process flow, mild reaction conditions, and convenience for factory production. The specific reaction equation is as follows:

[0043]

[0044] The amphiphilic diene monomer has both a hydrophilic group and a hydrophobic group, and the two olefin groups can undergo Michael addition reaction with thioether and amino groups with long alkyl chains to increase the hydrophobic effect of the system, so that an amphiphilic polymer can be prepared to achieve folding chain behavior in a hydrogel system. Due to the hydrophilic-hydrophobic interaction of the structural unit, the π-π stacking interaction of the benzene ring, and the hydrogen bond interaction within the system, the basic conditions for assembly are met, so that the amphiphilic polymer has a tendency to fold into a regular and orderly folded chain.

[0045] Preferably, the 3,5-diaminobenzoic acid is first added with ethyl acetate and potassium hydroxide solution, stirred and mixed, and then acryloyl chloride is dissolved in ethyl acetate and slowly added dropwise to the mixed solution in an ice water bath at 0-5°C.

[0046] Preferably, the molar ratio of 3,5-diaminobenzoic acid to potassium hydroxide is 1:2 to 2.2.

[0047] The advantages of the present invention are:

[0048] (1) The present invention provides an amphiphilic diene monomer, which simultaneously has a hydrophilic group, a hydrophobic group, a hydrogen bond interaction, and a π-π stacking interaction of a benzene ring, satisfying the basic conditions for assembly. The two olefin groups can obtain a long alkyl chain structure through a Michael addition reaction, increasing the hydrophilic and hydrophobic effects of the system, so that the folding chain behavior in the hydrogel system can be realized.

[0049] (2) The present invention provides a method for preparing an amphiphilic polymer, which is obtained by subjecting the amphiphilic diene monomer obtained above to Michael addition reaction with a long alkyl chain monomer containing a disulfide or a di-secondary amine.

[0050] (3) The present invention also provides a method for preparing a high-strength and high-toughness hydrogel, wherein the above-mentioned amphiphilic polymer is introduced into a hydrogel system. The amphiphilic polymer has double bonds at both ends, and after being uniformly mixed with a hydrogel monomer and a photoinitiator at a molecular level, a hydrogel based on the amphiphilic polymer is obtained by photoinitiated polymerization. The strength, stiffness and toughness of the hydrogel obtained by uniformly mixing the amphiphilic polymer prepared by the present invention with a hydrogel monomer and photoinitiated polymerization are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the H NMR spectrum of the amphiphilic diene monomer DBA prepared in Example 1 of the present invention;

[0052] Figure 2 This is the H NMR spectrum of the amphiphilic polymer PDBASH prepared in Example 1 of the present invention;

[0053] Figure 3 This is the H NMR spectrum of the amphiphilic polymer PDBANH prepared in Example 1 of the present invention;

[0054] Figure 4 is the stress-strain curve of the amphiphilic polymer prepared in Example 1 of the present invention;

[0055] Figure 5The mechanical properties test diagram of PAAM+x%PDBASH-nW (n is 3, 5, and 10, respectively) hydrogels constructed by amphiphilic polymers prepared in Examples 2 to 7, Examples 14 to 19, and Examples 26 to 29 of the present invention; wherein Figure 5 (ac) are stress-strain curves of PAAM+x%PDBASH–nW (n is 3, 5, and 10, respectively) hydrogels; Figure 5 (df) is the fracture energy change curve of PAAM+x%PDBASH–nW (n is 3, 5, and 10 respectively) hydrogel; Figure 5 (gi) is the change curve of elastic modulus of PAAM+x%PDBASH–nW (n in gi is 3, 5, and 10 respectively) hydrogel;

[0056] Figure 6 The mechanical properties test diagram of PAAM+x%PDBANH-nW (n is 3, 5, and 10, respectively) hydrogels constructed by amphiphilic polymers prepared in Examples 8-13, Examples 20-25, and Examples 30-33 of the present invention; wherein Figure 6 (ac) are stress-strain curves of PAAM+x%PDBANH–nW (n is 3, 5, and 10, respectively) hydrogels; Figure 6 (df) is the fracture energy change curve of PAAM+x%PDBANH–nW (n is 3, 5, and 10 respectively) hydrogel; Figure 6 (gi) is the elastic modulus change curve of PAAM+x%PDBANH–nW (n in the gi figure is 3, 5, and 10 respectively);

[0057] Figure 7 This is an electron microscope image of DBA self-assembly to form a two-dimensional structure;

[0058] Figure 8 Electron microscope pictures of the self-assembly of amphiphilic polymers PDBANH with molecular weights of 3W, 5W, and 10W (from top to bottom) prepared in Example 1 of the present invention to form a two-dimensional structure. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0061] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0062] The molecular weights described below are weight average molecular weights Mw.

[0063] Example 1

[0064] 1) Synthesis of amphiphilic diene monomers

[0065] Weigh 3,5-diaminobenzoic acid (3.043g, 0.02mol) into a round-bottom flask, add 100mL of ethyl acetate and 200mL of KOH aqueous solution (concentration of 11.8mg / mL) and stir to dissolve. Add acryloyl chloride (3.801g, 0.042mol) to 20mL of ethyl acetate and slowly drip into the round-bottom flask through a dropping funnel under an ice bath at 0-5°C. After the addition is complete, react for 4h. After the reaction is complete, adjust the pH to acidic with dilute hydrochloric acid (1M), and a purple-gray turbid precipitate will appear. Filter and wash with water to obtain the amphiphilic diene monomer DBA, whose structural formula is H NMR spectrum Figure 1 As shown;

[0066] 2) Synthesis of amphiphilic polymers

[0067] Weigh the amphiphilic diene monomer DBA (3g, 0.012mol) into a round-bottom flask, add 40mL DMF to dissolve, add 1,10-decanedithiol (2.4769g, 0.012mol) and tetramethylguanidine (0.2764g, 0.0024mol), stir and mix, and react at room temperature for 24h. After the reaction, precipitate in water to obtain a brown solid precipitate. Wash with water and freeze-dry to obtain the amphiphilic polymer PDBASH, with a yield of 72%, a molecular weight of 27W, and a hydrogen nuclear magnetic spectrum as shown in Figure 2 As shown, the polymer PDBASH structure is n is 636.

[0068] Weigh the amphiphilic diene monomer DBA (3g, 0.012mol) into a round-bottom flask, add 40mL DMF to dissolve, add N,N'-dimethyl-1,6-hexanediamine (1.755g, 0.012mol) and tetramethylguanidine (0.2764g, 0.0024mol), stir and mix, and react at 75℃ for 24h. After the reaction, precipitate in water to obtain a brown solid precipitate. Wash with water and freeze-dry to obtain the amphiphilic polymer PDBANH with a yield of 65%, a molecular weight of 23W, and a hydrogen nuclear magnetic spectrum as shown in Figure 3 As shown, the polymer PDBANH structure is n is 611.

[0069] The molecular weight of the amphiphilic polymer can also be regulated by controlling the feed ratio, thereby obtaining amphiphilic polymers with molecular weights of 30,000 (W), 50,000 (W), and 100,000 (W).

[0070]

[0071] According to the method for synthesizing the amphiphilic polymer in 2) above, only the amount of the amphiphilic diene monomer DBA is adjusted to (20 g, 0.08 mol), and the amount of 1,10-decanedithiol is adjusted to (16.038 g, 0.0777 mol), and the remaining steps are the same as 2), to obtain an amphiphilic polymer PDBASH with n of 71 and a molecular weight of 3W;

[0072] Only the amount of the amphiphilic diene monomer DBA in 2) is adjusted to (20 g, 0.08 mol), and the amount of 1,10-decanedithiol is adjusted to (16.224 g, 0.0786 mol), and the remaining steps are the same as 2), to obtain an amphiphilic polymer PDBASH with n of 118 and a molecular weight of 5W;

[0073] Only the amount of the amphiphilic diene monomer DBA in 2) was adjusted to (20 g, 0.08 mol), and the amount of 1,10-decanedithiol was adjusted to (16.368 g, 0.0793 mol), and the remaining steps were the same as 2), to obtain an amphiphilic polymer PDBASH with n of 235 and a molecular weight of 10W.

[0074] Only the amount of the amphiphilic diene monomer DBA in 2) was adjusted to (20 g, 0.08 mol), and the amount of N,N'-dimethyl-1,6-hexanediamine was adjusted to (11.252 g, 0.0780 mol), and the remaining steps were the same as 2), to obtain an amphiphilic polymer PDBANH with n of 80 and a molecular weight of 3W, and its electron microscope image is as follows Figure 8 As shown;

[0075] Only the amount of the amphiphilic diene monomer DBA in 2) was adjusted to (20 g, 0.08 mol), and the amount of N,N'-dimethyl-1,6-hexanediamine was adjusted to (11.368 g, 0.0788 mol), and the remaining steps were the same as 2), to obtain an amphiphilic polymer PDBANH with n of 133 and a molecular weight of 5W, and its electron microscope image is as follows Figure 8 As shown;

[0076] Only the amount of the amphiphilic diene monomer DBA in 2) was adjusted to (20 g, 0.08 mol), and the amount of N,N'-dimethyl-1,6-hexanediamine was adjusted to (11.454 g, 0.0794 mol), and the remaining steps were the same as 2), to obtain an amphiphilic polymer PDBANH with n of 266 and a molecular weight of 10W, and its electron microscope image is as follows Figure 8As shown;

[0077] 150.0 mg of the prepared amphiphilic polymers PDBASH and PDBANH were weighed and placed on a polytetrafluoroethylene film, and the upper and lower plates were hot-pressed at 100° C. for 5 min. The hot-pressed amphiphilic polymers PDBASH and PDBANH were placed in a manual hydraulic punching machine, cut into dumbbell-shaped specimens, and clamped in a universal tensile machine for mechanical property testing. Figure 4 The results show that the amphiphilic polymers PDBASH and PDBANH have strong mechanical properties.

[0078] Embodiments 2 to 33

[0079] Preparation of amphiphilic polymer hydrogels

[0080] Using DMF or water as solvent, weigh the amphiphilic polymer PDBASH / PDBANH and add it to DMF or water, heat and stir at 60-70°C for 3h to fully dissolve; weigh the dissolved PDBASH / PDBANH solution according to the molar ratio of amphiphilic polymer to acrylamide (AM, 800mg) of 0.005%-0.05%:1 and add it to a test tube containing acrylamide, and balance it to 2mL with DMF or water to ensure that the concentration of each embodiment is the same. Then add 100μL of photoinitiator 2-hydroxy-2-methylpropiophenone solution (HMPP). Among them, the concentration of HMPP in the 2-hydroxy-2-methylpropiophenone solution is 13mg / mL, and the molar ratio of the photoinitiator to the AM molar ratio is 7:10000. After mixing evenly, transfer the reaction solution to a polytetrafluoroethylene mold and irradiate it with a UV lamp with a wavelength of 395nm at room temperature for 20min to obtain a high-strength and high-toughness hydrogel, that is, the amphiphilic polymer hydrogel.

[0081] The specific formulas for preparing the hydrogels according to the above method Examples 2 to 13 are shown in Tables 1 and 2;

[0082] Table 1 Specific formula of PAAM+x%PDBASH-3W hydrogel

[0083]

[0084] Table 2 Specific formula of PAAM+x%PDBANH-3W hydrogel

[0085]

[0086] The specific formulas for preparing the hydrogels in Examples 14 to 25 are shown in Tables 3 and 4;

[0087] Table 3 Specific formula of PAAM+x%PDBASH-5W hydrogel

[0088]

[0089] Table 4 Specific formula of PAAM+x%PDBANH-5W hydrogel

[0090]

[0091] The specific formulas for preparing the hydrogels in Examples 26 to 33 are shown in Tables 5 and 6;

[0092] Table 5 PAAM + x% PDBASH-10W hydrogel specific formula

[0093]

[0094] Table 6 PAAM + x% PDBANH-10W hydrogel specific formula

[0095]

[0096] In the preparation process of the above hydrogel, when the molar ratio of the amphiphilic polymer doping amount to the AM molar ratio is x%:1=0.1%:1, the color of the reaction solution is dark gray, which affects the photopolymerization effect and the gel cannot be obtained by photopolymerization.

[0097] Hydrogel mechanical properties testing

[0098] The hydrogel was placed in a manual hydraulic punching machine, cut into dumbbell-shaped specimens, and clamped in a universal tensile machine for mechanical property testing.

[0099] like Figure 5 As shown in the figure, the strength of the polyacrylamide (PAAM) hydrogel (PAAM+x%PDBASH–nW (n is 3, 5, 10)) constructed by introducing amphiphilic PDBASH polymers is significantly improved, and the strength of the hydrogel gradually increases with the increase of the amount of amphiphilic PDBASH polymers; among them, the strength of the PAAM hydrogel introduced with 0.05% monomer molar amount of PDBASH-3W is 46.8 times higher than that of the PAAM+0.02% BIS hydrogel cross-linked with the traditional chemical crosslinker BIS; but due to the relatively hydrophobic molecular structure of the PDBASH polymer, there is a poor solubility in the process of PAAM hydrogel construction, so the introduction of PDBASH polymer does not significantly improve the fracture strain and toughness of the PAAM hydrogel. However, the mechanical properties of the PAAM+x%PDBASH–nW (n is 3, 5, 10) hydrogel still show molecular weight dependence, and the strength and stiffness increase with the increase of the molecular weight of the introduced amphiphilic polymer.

[0100] Based on the results of strengthening and toughening hydrogels constructed with amphiphilic PDBASH polymers, the molecular structure of the amphiphilic polymers was designed and adjusted, and the amphiphilic polymer PDBANH was obtained by Michael addition reaction with the protonable monomer N,N'-dimethyl-1,6-hexanediamine. PAAM hydrogels were constructed by adding different molar amounts of amphiphilic polymer PDBANH, and the mechanical properties were tested. Figure 6 The results show that the strength, stiffness and toughness of PAAM hydrogels (PAAM+x%PDBANH–nW (n is 3, 5, 10)) constructed with the introduction of amphiphilic polymer PDBANH are significantly improved, and the strength, stiffness and toughness increase with the increase of the amount of amphiphilic polymer PDBANH. Among them, the PAAM hydrogel with the addition of 0.03% PDBANH-5W polymer has a 28.3-fold increase in strength, a 10-fold increase in fracture strain, and a 261.7-fold increase in toughness compared with the PAAM+0.02% BIS hydrogel cross-linked with the traditional chemical cross-linker BIS. The mechanical properties of PAAM+x%PDBANH–nW (n is 3, 5, 10) hydrogels increase with the increase of the molecular weight of the introduced amphiphilic polymer.

[0101] Weigh the amphiphilic diene monomer DBA (3 g, 0.012 mol) and NaOH (0.48 g, 0.012 mol) in a round-bottom flask, add 40 mL of water to fully dissolve; add potassium persulfate (0.032 g, 0.0001 mol), and polymerize at 70°C for 8 h. After the reaction, dialyze the reaction solution for 48 h and freeze-dry. DBA self-assembles to form a two-dimensional structure, as shown in the electron microscope image. Figure 7 As shown, it can be seen that the amphiphilic diene monomer DBA has hydrophilic-hydrophobic interactions, π-π stacking interactions of benzene rings and hydrogen bonding interactions within the system, which gives it the ability to self-assemble in the aqueous phase and also provides power for the folding of the amphiphilic polymer.

[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An amphiphilic polymer, characterized in that: Its structural formula is one of the following: Wherein, n is 70-636, and R is a saturated fatty alkyl group.

2. The amphiphilic polymer according to claim 1, characterized in that: n=70-266。 3. The amphiphilic polymer according to claim 1 or 2, characterized in that: Its weight average molecular weight is 30,000-270,000; R in the structural formula is -(CH2) 10 -or -(CH2)6-.

4. A method for preparing an amphiphilic polymer as claimed in any one of claims 1 to 3, characterized in that: Including amphiphilic diene monomer The amphiphilic polymer is obtained by a Michael addition reaction with an alkyl monomer containing a disulfide group or an alkyl monomer containing a di-secondary amine group; wherein the structural formula of the alkyl monomer containing a disulfide group is The structural formula of the alkyl monomer containing di-secondary amine groups is R is a saturated fatty alkyl group.

5. The method for preparing an amphiphilic polymer according to claim 4, characterized in that: The molar ratio of the amphiphilic diene monomer, the disulfide group-containing alkyl monomer or the di-secondary amine group-containing alkyl monomer is 1-1.2:

1.

6. The method for preparing an amphiphilic polymer according to claim 4, characterized in that: The temperature for the reaction of the amphiphilic diene monomer with the alkyl monomer containing a disulfide group is room temperature, and the time is 24 hours; the temperature for the reaction of the amphiphilic diene monomer with the alkyl monomer containing a di-secondary amine group is 70-80°C, and the time is 24 hours; the alkyl monomer containing a disulfide group is 1,10-decanedithiol; the alkyl monomer containing a di-secondary amine group is N,N'-dimethyl-1,6-hexanediamine; the initial concentration of the amphiphilic diene monomer in the system is between 20 mg / mL and 100 mg / mL.

7. Use of the amphiphilic polymer according to any one of claims 1 to 3 in preparing a hydrogel.

8. A high-strength and high-toughness hydrogel, characterized in that: The method is prepared from raw materials comprising the amphiphilic polymer described in any one of claims 1 to 3 and a hydrogel monomer.

9. A method for preparing a high-strength and high-toughness hydrogel as claimed in claim 8, characterized in that: The method comprises taking amphiphilic polymer and hydrogel monomer as raw materials and performing photo-initiated polymerization reaction to obtain the high-strength and high-toughness hydrogel.

10. The method for preparing a high-strength and high-toughness hydrogel according to claim 9, characterized in that: The molar ratio of the amphiphilic polymer to the hydrogel monomer is 1:2000-20000; the molar ratio of the photoinitiator to the hydrogel monomer is 7:10000; and the hydrogel monomer is acrylamide.

Citation Information

Patent Citations

  • pH-responsive degradable hydrogel and preparation method thereof

    CN102070784A

  • Preparation method and application of microenvironment response type polymer prodrug co-delivery gel system

    CN113679662A

  • Amphiphilic polysiloxane prepolymers and uses thereof

    US20120029111A1

  • Polymerizable chain-extended polysiloxanes with pendant hydrophilic groups

    US20120088843A1

  • Porous sorptive solid phase microextraction devices and preparation thereof

    US20240181430A1

Cited By

  • Two-dimensional amphiphilic polymer coating, coating and preparation method

    CN120248694A